Teaching Methods of Biological Values and Entrepreneurship at Home Tahfidz Entrepreneur - Arfandi; Agus Supriyadi; Ahmad Juandi (Faculty of Education and Teacher Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2024)
Home Tahfidz Entrepreneur (HTE) Sekarbela Mataram is proof that there is a new breakthrough or new innovation in the field of education that offers a combined concept of education and entrepreneurship in order to create a quality social order, namely education and an advanced economy. The purpose of this study is to characterize the teaching of religious values and the style of teaching entrepreneurial principles at Home Tahfidz Entrepreneur. This research is a qualitative case study, with data collected through observation, interviews, and documentation. The topics researched included Tahfidz House leaders, instructors, and students. Meanwhile, source triangulation is utilized to ensure that the data is accurate. The research results show that the pattern of teaching religious values through activities is: a) daily congregational tahajjud prayer, congregational morning prayer, reading wirid al-ma'tsurat, morning study halaqoh, HTE students' khidmah, memorization deposit activities; b) weekly recitation meeting activities, Islamic jurisprudence, and Arabic language training; c) monthly Tasmi' memorized; d) semester Memorization Exam; e) annual Holiday Tahfidz Camp (HTC), Al-Qur'an Second, the pattern of teaching entrepreneurial values at Home Tahfidz Entrepreneur (HTE) Sekarbela Mataram is obtained via activities: a) daily Pawon Santri (Culinary Arts), Pawon Anak Santri (Marketing the kids' work); b) weekly study of entrepreneurs, Galang, and HTE LAZ DASI; c) annual students of THE takjil menu every month of Ramadhan.